IMPLEMENTASI MORNING ASSEMBLY SEBAGAI STRATEGI PENGUATAN KARAKTER SISWA DI SEKOLAH DASAR - Arrum Dwi Wahyuni; Ahmad Hariandi; Desy Rosmalinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of morning assembly as a strategy to strengthen student character at SDN 14/I Sungai Baung. The research was conducted using a case study approach with data obtained through observation, interviews, and documentation. The findings reveal that morning assembly serves as a structured routine that contributes to building student discipline, responsibility, respect, religiosity, and patriotism. The implementation includes activities such as lining up, praying, singing national songs, delivering moral messages, and providing school information. The strategy for character strengthening is carried out through teacher modeling, habituation, direct supervision, moral reinforcement, positive feedback, and student involvement as assembly officers. The study also identifies several obstacles, including student tardiness, inconsistency in line discipline, lack of support from home routines, and weather disturbances. Despite these constraints, morning assembly has a significant positive impact on improving student discipline and creating a more conducive school environment. The results of this study highlight the importance of habitual school routines as an effective means of character education in elementary schools.